Klatskin-Like Lesions. (28th June 2012) - Senthil Kumar, M. P.; Marudanayagam, R.
Abstract : Hilar cholangiocarcinoma, also known as Klatskin tumour, is the commonest type of cholangiocarcinoma. It poses unique problems in the diagnosis and management because of its anatomical location. Curative surgery in the form of major hepatic resection entails significant morbidity. About 5–15% of specimens resected for presumed Klatskin tumour prove not to be cholangiocarcinomas. There are a number of inflammatory, infective, vascular, and other pathologies, which have overlapping clinical and radiological features with a Klatskin tumour, leading to misinterpretation. This paper aims to summarise the features of such Klatskin-like lesions that have been reported in surgical literature.